A New Narcissus Named “Lygdamus”: A Poetical Source for a Different Interpretation of Michelangelo’s Crouching Youth from the Collection of the State Hermitage - Perini Folesani, Giovanna (Actual Problems of Theory and History of Art, 2016)
The discovery in a well-known manuscript preserved in the Bologna University Library of three still unpublished poems in Latin (epigrams) by an obscure 16th century poet called Giovan Francesco Fabri sheds some new light on the appreciation of Michelangelo’s sculptures amidst his contemporaries. The essay unravels their connections with the Florentine debate on Michelangelo’s work, especially in Varchi’s and Doni’s literary oeuvre. In particular, one of Fabri’s epigrams seems to describe the Crouching Youth at the Hermitage, thus proving that it is an autograph work and that it was conceived as (or at any rate early taken for) an autonomous work of art. Besides, the essay refers to recent archaeological literature suggesting that in the 17th century the statue was kept in Villa Medici, Rome. It also offers an attempt to give some biographical and cultural substance to the author of these poems, Giovan Francesco Fabri, now almost forgotten, but somewhat famous in his days for his Italian poems.